Extra-/intracellular biosynthesis of gold nanoparticles by an alkalotolerant fungus, trichothecium sp. - Ahmad, Absar; Senapati, Satyajyoti; Khan, Mohammad Islam; Kumar, Rajiv; Sastry, Murali (Journal of Biomedical Nanotechnology, 2005)
The development of reliable, eco-friendly processes for the synthesis of nanoscale materials is an important aspect of nanotechnology. As part of our ongoing investigation into the use of fungi for nanoparticle synthesis, we report herein that depending on the reaction conditions of the fungus Trichothecium sp. with aqueous gold ions, gold nanoparticle synthesis can be controlled to occur either within the biomass or extracellularly. Moreover, we have found that reaction of gold ions with the Trichothecium sp. fungal biomass under stationary conditions results in the rapid extracellular formation of gold nanoparticles of spherical, rod-like and triangular morphology whereas reaction of the biomass under shaking conditions resulted in intracellular growth of the nanoparticles. It is believed that on changing the reaction conditions of the fungus with gold ions, the enzymes and proteins which are being released into the medium under stationary conditions do not get released under shaking conditions resulting in the formation of extracellular or intracellular gold nanoparticles respectively. The gold nanoparticles are not toxic to the cells and the cells continued to grow after the biosynthesis of the gold nanoparticles in both the cases.
Keywords: Biosynthesis; enzymes; Fungus; Gold; Morphology Control; Nanoparticles

Extracellular biosynthesis of platinum nanoparticles using the fungus fusarium oxysporum - Syed, Asad; Ahmad, Absar (Colloids and Surfaces B-Biointerfaces, 2012)
Nanoscience is a blooming field and promises a better future. In order to fabricate nanoparticles in an eco-friendly and inexpensive manner, significant efforts are being made to replace the chemical and physical methods currently being used with the biological methods. Chemical methods are toxic while the physical ones are very expensive. Biological methods, apart from being cost-effective, also provide protein capped nanoparticles which are thus very stable, have good dispersity and do not flocculate, and may find use in various applications. The present work emphasizes on platinum nanoparticles synthesis protocol which occurs at ambient conditions. The fungus Fusarium oxysporum when incubated with hexachloroplatinic acid (H2PtCl6) in ambient conditions reduces the precursor and leads to the formation of stable extracellular platinum nanoparticles. The biosynthesis of platinum nanoparticles was monitored by UV-visible spectroscopy and these nanoparticles were completely characterized by transmission electron microscopy (TEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The nanoparticles are in the size range of 5-30 nm and are stabilized by proteins present in the solution. The reduction process is believed to occur enzymatically, thus creating the possibility of a rational, fungal-based method for the synthesis of nanoparticles over a wide range of chemical compositions. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biosynthesis; Fungus; Nanoparticles; platinum

Transformation of (+/-)-lavandulol and (+/-)-tetrahydrolavandulol by a fungal strain Rhizopus oryzae - Daramwar, Pankaj P.; Rincy, Raju; Niloferjahan, Siddiqui; Krithika, Ramakrishnan; Gulati, Arvind; Yadav, Amit; Sharma, Rakesh; Thulasiram, Hirekodathakallu V. (Bioresource Technology, 2012)
Biotransformation of an irregular monoterpene alcohol, (+/-)-lavandulol [(+/-)-5-methyl-2-(1-methylethenyl)-4-hexen-1-ol] (I) and its tetrahydro derivative, (+/-)-tetrahydrolavandulol [(+/-)-2-isopropyl-5-methylhexan-1-ol] (II) were studied using a soil isolated fungal strain Rhizopus oryzae. Five metabolites, 2-((3,3-dimethyloxiran-2-yl)methyl)-3-methylbut-3-en-1-ol (Ia), 2-methyl-5-(prop-1-en-2-yl)hex-2ene-1,6-diol (Ib), 2-methyl-5-(prop-1-en-2-yl)hexane-1,6-diol (Ic), 2-(3-methylbut-2-enyl)-3-methylenebutane-1,4-diol (Id), 5-methyl-2-(2-methyloxiran-2-yl)hex-4-en-1-01 (Ie) have been isolated from the fermentation medium and characterized with lavandulol as a substrate. When tetrahydrolavandulol used as a substrate, two metabolites 2-isopropyl-5-methylhexane-1,5-diol (IIa) and 2-isopentyl-3-methylbutane-1,3-diol (lib) have been isolated from the fermentation medium. Biotransformation studies with R. oryzae clearly indicate that the organism initiates the transformation either by hydroxylation at allylic methyl groups or epoxidation of double bond. GC and GCMS analyses indicated that both (R)and (S)-enantiomers of I and II have been transformed into corresponding hydroxylated or epoxy derivatives, when racemic I and II were used as substrates. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biotransformation; Fungus; Lavandulol; Rhizopus oryzae; Tetrahydrolavandulol

Biological synthesis of silver nanoparticles using the fungus humicola sp and evaluation of their cytoxicity using normal and cancer cell lines - Syed, Asad; Saraswati, Supriya; Kundu, Gopal C.; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
Nanoscience is a new born science of the modern era and taps into the potential of particles at nanoscale. Bulk materials reduced to nanoscale dimensions thus obtain unique properties such as electronic, optical, magnetic and chemical. As far as synthesis of nanoparticles is concerned, biological synthesis has recently sparked a great interest as compared to other available chemical and physical methods on account of its eco-friendliness and cost-effectiveness. Here we report, for the first time, the biosynthesis of silver nanoparticles by the thermophilic fungus Humicola sp. The fungus when reacted with Ag+ ions reduces the precursor solution and leads to the formation of extracellular nanoparticles as monitored by ultra violet visible spectroscopy (UV-Vis). The morphology of nanoparticles is found to be spherical with good dispersity as revealed by transmission electron microscopy (TEM). Cell viability assays were carried out to assess the cytotoxicity of silver nanoparticles on NIH3T3 mouse embryonic fibroblast cell line and MDA-MB-231 human breast carcinoma cell line. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Cell viability; Fungus; Humicola sp.; Nanoparticles; Silver

Extracellular biosynthesis of CdTe quantum dots by the fungus fusarium oxysporum and their anti-bacterial activity - Syed, Asad; Ahmad, Absar (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2013)
The growing demand for semiconductor [quantum dots (Q-dots)] nanoparticles has fuelled significant research in developing strategies for their synthesis and characterization. They are extensively investigated by the chemical route; on the other hand, use of microbial sources for biosynthesis witnessed the highly stable, water dispersible nanoparticles formation. Here we report, for the first time, an efficient fungal-mediated synthesis of highly fluorescent CdTe quantum dots at ambient conditions by the fungus Fusarium oxysporum when reacted with a mixture of CdCl2 and TeCl4. Characterization of these biosynthesized nanoparticles was carried out by different techniques such as Ultraviolet-visible (UV-Vis) spectroscopy, Photoluminescence (PL), X-ray Diffraction (XRD), X-ray Photoelectron spectroscopy (XPS), Transmission Electron Microscopy (TEM) and Fourier Transformed Infrared Spectroscopy (FTIR) analysis. CdTe nanoparticles shows antibacterial activity against Gram positive and Gram negative bacteria. The fungal based fabrication provides an economical, green chemistry approach for production of highly fluorescent CdTe quantum dots. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: antibacterial activity; Biosynthesis; CdTe; Fungus; Nanoparticles

Biological synthesis of alpha-Ag2S composite nanoparticles using the fungus Humicola sp. and its biomedical applications - Syed, Asad; Saedi, Marzouq Hussain Al; Bahkali, Ali H.; Elgorban, Abdallah M.; Kharat, Maheshkumar; Pai, Kalpana; Ghodake, Gajanan; Ahmad, Absar (Journal of Drug Delivery Science and Technology, 2021)
Synthesis of alpha-Ag2S (silver sulfide) is a highly challenging task, usually attempted using synthetic, hazardous chemical processes. This report puts efforts to exploring microbial-based eco-friendly alternatives. A facile, onepot biological method for the synthesis of alpha-Ag2S composite nanoparticles (NPs) in an aqueous medium at ambient conditions was established. As prepared alpha-Ag2S composite NPs were efficiently produced from precursors silver nitrate and sodium sulfite. The extracellular biomolecules produced by Humicola sp. reduced the precursor solution and at the same time it capped the formed Ag2S NPs. The characterization performed by different techniques revealed excellent optical, morphological, and structural properties (size, shape distribution, and crystallinity) of the alpha-Ag2S NPs. The change in color from colorless to dark brown indicated the formation of alpha-Ag2S, which was further confirmed by fluorescence and UV-Visible spectroscopy, showing a sharp peak at 410 nm. Morphological analysis of alpha-Ag2S NPs confirmed the spherical shape, and narrow size distribution. alpha-Ag2S NPs were found to be potent in antimicrobial applications owing to their high dispersibility in water and capping by extracellular biomolecules secreted by Humicola sp. The anti-cancer activity for alpha-Ag2S performed using human breast cancer cell line (ZR-75-1) and human Burkitt's lymphoma cancer (Daudi). The biocompatibility test was performed using human peripheral blood mononuclear cells (PBMCs) for alpha-Ag2S NPs. The anti-leishmania activity was also determined for alpha Ag2S NPs in-vitro using the standard anti-promastigote protocol (Leishmania donovani promastigotes). This extracellular system is an economically and environmentally benign route for the biosynthesis of alpha-Ag2S NPs having desired surface, structure and biomedical properties.
Keywords: Cytotoxicity; Fungus; Hemolysis; Humicolasp; Silver sulfide(alpha-Ag2S)

Bi(OTf)3-promoted cascade annulation of hydroxy-pyranones and unsaturated γ-ketoesters for the construction of polycyclic bridged pyrano-furopyranones - Rathod, Akshay B.; Borade, Balasaheb R.; Sambherao, Pooja I.; Kontham, Ravindar (Organic and biomolecular chemistry, 2024)
An efficient protocol for constructing complex three dimensional polycyclic bridged chromano-furopyranones and pyrano-furopyranones (closely related to bioactive natural products) via bismuth(III)-catalyzed cascade annulation of hydroxy-pyranones and unsaturated gamma-ketoesters is presented. This process involves intermolecular Michael addition, intramolecular hemiketalization, lactonization, formation of one C-C bond and two C-O bonds, rings, and contiguous stereocenters.
Keywords: 1 3-Dicarbonyl Compounds; alkynols; Coumarins; Fungus